2015
DOI: 10.1210/jc.2014-3130
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Mutations of Human Corticosteroid-Binding Globulin

Abstract: Our data provide insight into how specific residues affect CBG secretion or function and illustrate the need to consider the various naturally occurring human CBG mutations in clinical evaluations of diseases associated with abnormalities in cortisol levels or activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…The steroid-binding activity of CBG is undetectable in rat plasma samples in which CBG appears to be have undergone proteolysis, and this is in line with a marked loss in cortisol-binding affinity observed when the RCL of human CBG is cleaved by neutrophil elastase (Hammond , et al 1990), chymotrypsin (Simard , et al 2015) or the bacterial proteinase, LasB (Simard , et al 2014). However, our observations of in vivo rat CBG proteolysis under pathophysiological conditions contrasts with a previous report that E-coli produced rat CBG, mutated to allow for cleavage by human neutrophil elastase, only undergoes a 2-fold reduction in binding affinity (Gardill , et al 2012).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The steroid-binding activity of CBG is undetectable in rat plasma samples in which CBG appears to be have undergone proteolysis, and this is in line with a marked loss in cortisol-binding affinity observed when the RCL of human CBG is cleaved by neutrophil elastase (Hammond , et al 1990), chymotrypsin (Simard , et al 2015) or the bacterial proteinase, LasB (Simard , et al 2014). However, our observations of in vivo rat CBG proteolysis under pathophysiological conditions contrasts with a previous report that E-coli produced rat CBG, mutated to allow for cleavage by human neutrophil elastase, only undergoes a 2-fold reduction in binding affinity (Gardill , et al 2012).…”
Section: Discussionmentioning
confidence: 54%
“…Genome-wide sequencing of human populations has also identified numerous other single nucleotide polymorphisms that cause decreased CBG production or defects in steroid binding, some of which are enriched in specific ethnic groups (Simard , et al 2015). Although patients with CBG deficiencies have been reported to suffer from a variety of symptoms including chronic pain, fatigue, depression, hypotension and excess body weight (Gagliardi , et al 2010), it remains to be determined how well they cope with severe, acute inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…With only six matched tumor and normal DNA pairs, Pasqualucci et al 13 already identified by whole-exome sequencing 106 rare germline variants among which the SERPINA6 gene. This gene is involved in corticosteroid bioavailability by encoding corticosteroid-binding globulin 92 and it is also targeted by somatic mutations in DLBCL (Supplementary Table s1). Many of the germline variants described by Pasqualucci et al belong to the same functional classes of genes that are somatically mutated in this disease and could well be relevant for its development.…”
Section: Genes With Less Obvious Causalitymentioning
confidence: 99%
“…Hypoalbuminemia and alterations in the binding of cortisol may lead to subnormal total cortisol responses to ACTH, while the free cortisol response can remain entirely normal in subjects with severe acute illness [9]. Other examples in which free cortisol measurement becomes particularly important are the rare cases of inactive corticosteroid-binding globulin, such as CBG-Lyon [10] or congenital CBG deficiency [11,12]. The current consensus is that the free rather than the protein-bound fraction of cortisol is responsible for its physiological function [4].…”
Section: Introductionmentioning
confidence: 99%